Cost effectiveness of pomalidomide in patients with relapsed and refractory multiple myeloma in Sweden. (3rd May 2016) - Borg, Sixten; Nahi, Hareth; Hansson, Markus; Lee, Dawn; Elvidge, Jamie; Persson, Ulf
Abstract: Background : Multiple myeloma (MM) patients who have progressed following treatment with both bortezomib and lenalidomide have a poor prognosis. In this late stage, other effective alternatives are limited, and patients in Sweden are often left with best supportive care. Pomalidomide is a new anti-angiogenic and immunomodulatory drug for the treatment of MM. Our objective was to evaluate the cost effectiveness of pomalidomide as an add-on to best supportive care in patients with relapsed and refractory MM in Sweden. Material and methods : We developed a health-economic discrete event simulation model of a patient's course through stable disease and progressive disease, until death. It estimates life expectancy, quality-adjusted life years (QALYs) and costs from a societal perspective. Effectiveness data and utilities were taken from the MM-003 trial comparing pomalidomide plus low-dose dexamethasone with high-dose dexamethasone (HIDEX). Cost data were taken from official Swedish price lists, government sources and literature. Results : The model estimates that, if a patient is treated with HIDEX, life expectancy is 1.12 years and the total cost is SEK 179 976 (€19 100), mainly indirect costs. With pomalidomide plus low-dose dexamethasone, life expectancy is 2.33 years, with a total cost of SEK 767 064 (€81 500), mainly in drug and indirect costs. Compared to HIDEX, pomalidomide treatment gives a QALY gain of 0.7351 and an incremental cost of SEK 587 088 (€62 400) consisting of increased drug costs (59%), incremental indirect costs (33%) and other healthcare costs (8%). The incremental cost-effectiveness ratio is SEK 798 613 (€84 900) per QALY gained. Conclusion : In a model of late-stage MM patients with a poor prognosis in the Swedish setting, pomalidomide is associated with a relatively high incremental cost per QALY gained. This model was accepted by the national Swedish reimbursement authority TLV, and pomalidomide was granted reimbursement in Sweden.